Analysis of the performance of post-lingually deafened patients with Nurotron® Venus™ cochlear implants. (June 2014) - Li, Jianan; Ji, Fei; Chen, Wei; Zhao, Hui; Han, Dongyi; Yang, Shiming
Abstract Objective: The aim of this study was to analyze the safety and effectiveness of a new cochlear implant (CI) system developed in China, the Nurotron Venus device. Material and methods: Fifteen post-lingually deafened patients received Nurotron Venus CIs in our hospital. The safety and effectiveness of the devices were evaluated within 2 years after implantation. Patients' hearing thresholds were assessed. In addition, the speech perception performance of Nurotron Venus CI recipients was compared with that of 15 Cochlear Nucleus CI24 recipients. Results and conclusion: During 2 years of observation, all the Nurotron recipients used their devices regularly and effectively. The aided hearing thresholds of all the recipients were within the speech spectrum. The average scores of HOPE sentences and HOPE monosyllable words tests among Nurotron CI recipients were 82.88 ± 21.40% and 56.67 ± 9.77%, respectively. The average scores among Cochlear Nucleus CI24 recipients were 87.33 ± 14.44% and 52.8 ± 12.76%, respectively. There was no statistically significant difference in the speech test scores between these two groups when assessed using the t test. The Nurotron Venus cochlear implant system worked safely and effectively. The speech perception of Nurotron recipients was similar to that of the other CI system recipients.